2009 IEEE Symposium on Industrial Electronics &Amp; Applications 2009
DOI: 10.1109/isiea.2009.5356419
|View full text |Cite
|
Sign up to set email alerts
|

Assessing combinatorial interaction strategy for reverse engineering of combinational circuits

Abstract: T-way test data generators play an immensely important role for both hardware and software configuration testing. Earlier work concludes that t-way test data generator can achieve 100% coverage without having to regard for more than 6 way interactions. In this paper, we investigate whether or not such a conclusion can be applicable for reverse engineering of combinational circuits. In this case, we reverse engineer a faulty commercial eight segment display controller using our t-way test data generator in orde… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
3
1
1

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 21 publications
0
3
0
Order By: Relevance
“…GMIPOG is a combinatorial test generator based on specified inputs and parameter interaction. Running on a Grid environment, GMIPOG adopts both the horizontal and vertical extension mechanism (i.e., similar to that of IPOG [3]) in order to derive the required test suite for a given interaction strength [9]. GMIPOG supports high degree of interaction and can be run in cumulative mode (i.e., support one-test-at-a-time approach with the capability to vary t automatically until the exhaustive testing is reached) [9].…”
Section: Related Workmentioning
confidence: 99%
“…GMIPOG is a combinatorial test generator based on specified inputs and parameter interaction. Running on a Grid environment, GMIPOG adopts both the horizontal and vertical extension mechanism (i.e., similar to that of IPOG [3]) in order to derive the required test suite for a given interaction strength [9]. GMIPOG supports high degree of interaction and can be run in cumulative mode (i.e., support one-test-at-a-time approach with the capability to vary t automatically until the exhaustive testing is reached) [9].…”
Section: Related Workmentioning
confidence: 99%
“…Based on empirical evidence in four application domains (involving medical devices, a web browser, an HTTP server, and a NASA-distributed database application [32,33]), Kuhn et al concluded that all faults in any typical software system can be detected at t = 6. Using a different application domain, Younis and Zamli demonstrated that only after t = 7 can the behavior of the combinatorial circuits of interest be predicted for reverse engineering applications [59].…”
Section: Introductionmentioning
confidence: 99%
“…Zamli et al [24] presented a similar idea and proposed GTWay addresses, the generation of test data for a high-covering strength t > 6. In a different application domain, Younis and Zamli [25] demonstrated that the behaviour of the combinatorial circuits of interest could be predicted for reverse engineering applications only after t = 7. Recently, a few methods that can support covering strength higher than six have been proposed [18,[26][27][28].…”
mentioning
confidence: 99%